(untitled) (Cultura Económica, 2018)
This article aims to provide anthropological foundations of the application of usury according to Francisco de Vitoria. In the first place, the author describes and contextualizes both pre-modern and modern economic approaches and principles. Secondly, she presents characteristics of usury practices in loans of money or other goods with charges according to Vitoria. To conclude, the article offers a detailed definition about the meaning of “lend” and its implications in economic and social domains.